Anthropology is the subject of science and its scientific status (Journal of Philosophy Culture and Political Science, 2018)
Anthropology is the history of mankind, the scientific study of human culture. Letter wordshuman science. real, from the point of view of historical significance, social and biological population scientific description for the study branch of knowledge.